Bridging Knowledge, Attitudes, and Practices: Hand Hygiene Behaviour Among Nursing Students - Nor Fadhilah Abdullah; Balqis Humaira Ahmad; Hasnora Safira Aida Muhd Razali (Fundamental and Management Nursing Journal, 2026)
Introduction: Healthcare-associated infections remain a major threat to patient safety. Hand hygiene is one of the most effective ways to prevent these infections. Nursing students’ ability to apply appropriate hand hygiene practices has important implications for patient safety and quality of care. This study aimed to analyse the knowledge, attitudes, and practices (KAP) related to hand hygiene among nursing students at Universiti Sultan Zainal Abidin, Malaysia. Method: A cross-sectional study was conducted with 136 Diploma and Bachelor nursing students selected through simple random sampling. Data were collected using a structured questionnaire based on the validated World Health Organization’s hand hygiene tool of knowledge, attitude and practice, and distributed via Google Forms. Data analysis was done using SPSS version 29, including descriptive and bivariate analysis. Results: All 136 students responded (100%). Most were female (n = 120, 88.2%). The average scores for knowledge, attitude, and practice were 18.05 (SD = 1.657), 5.33 (SD = 2.157), and 4.02 (SD = 1.503), respectively. The year of study was significantly associated with knowledge (p = 0.003), attitude (p = 0.002), and practice (p < 0.001). Education level also showed a significant relationship with attitude (p = 0.004). Conclusion: The findings show that academic level and clinical exposure significantly affect nursing students’ hand hygiene behavior. Continuous education and practical training are crucial to improving hand hygiene compliance. Understanding the link between demographics and KAP can support the development of targeted strategies to reduce the risk of HAIs in clinical practice.